HUBUNGAN ANTARA AKTIVITAS BELAJAR SISWA DAN HASIL BELAJAR PADA MATA PELAJARAN KIMIA KELAS X SMA NEGERI 5 PONTIANAK - Nuraini Nuraini; Fitriani Fitriani; Raudhatul Fadhilah (Universitas Muhammadiyah Pontianak, 2018)
Learning activity was a student’s activeness in learning process to achieve outcome and aim of learning which had been determined. This research aimed to describe the degree of student’s learning activity, its outcome and the correlation between them. Collecting data used purposive sampling technique which used 36 students of class XB as a sample. The data of student’s learning activity was analyzed by using observation checklist. The observation result showed that the mean of student’s learning activity was 51,76 % with the category of active enough. The result of second term examination 2016/2017 showed that the mean of student’s score was 40,42 as less good category. The correlation between students’ learning activity and its outcome was analyzed by the correlation of product moment formula. The result of analyzing data showed that there was positive correlation between students’ learning activity and outcome in chemistry X class at SMA Negeri 5 Pontianak with correlation coefficient 0,67 as high category. The contribution of students’ learning activity and outcome was obtained coefficient of determination (r2) equal to 0,451. Thus, it could be concluded that there was a influence and positive relationship with the strong category between student learning activities and learning outcomes in chemistry class X at SMA Negeri 5 Pontianak.Keywords : Students’ learning activity, Students’ learning outcome, Chemistry